A study on BOLD fMRI of the brain basic activities of MDD and the first-degree relatives. (1st September 2020) - Song, Yulu; Shen, Xiaojun; Mu, Xinnuan; Mao, Ning; Wang, Bin
Abstract: Introduction: The present study aims to explore the characteristics and differences of the ReHo, ALFF and fALFF of brain in the resting state of depression and first-degree relatives, in order to identify candidate central prodromal biomarkers of depression. Method: Three groups of medication-free patients (39–59 years old) was involved in this study, including the patients with major depression disorder (MDD group, n  = 15), healthy volunteers with first-degree relatives with MDD (first-degree relatives group, n  = 15), healthy volunteers with no personal or family history of MDD (the control group [HC], n  = 15). Participants underwent functional MRI while staying in a resting state after a conventional MRI scanning on a clinical 3 T system(Siemens Skyra, Germany). Results: The ReHo, ALFF and fALFF values are different in brain of MDD, first-degree relatives, and HC ( p <.05). MDD patients exhibited abnormal spontaneous activity in multiple brain regions which are closely related to emotion regulation and perception. The present findings provide further insight into the pathological mechanisms underlying MDD. Conclusion: With the widespread abnormal values of brain in MDD and first-degree relatives measured, we can get a hypothesis that these abnormalities may be associated with cognitive network disorders and emotional distress in MDD. Key points: The fMRI could increase the early validity of MDD as a new diagnostic and disease-monitoring tool. Monitoring ReHo, ALFF, fALFF values using fMRI can provide insight into the presence and evolution of MDD disease and permit objective evaluation of brain abnormalities. It appears that ReHo, ALFF, fALFF could be used as markers for monitoring disease progression and treatment effects in MDD patients in the future.